EXPLORATION OF THE ISLAMIC RELIGIOUS EDUCATION SYSTEM AT SMK NEGERI 1 REJANGLEBONG TO FORM A QUR'ANI GENERATION - Lukman Asha (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
Education is not just an activity of transferring knowledge from educators to students. Equipping children with the values contained in Al Qur’an is very important given at an early age. The process of fostering student character to realize the Qur'anic generation has been implemented at SMK Negeri 1 Rejang Lebong. Therefore, the researchers were interested in exploring the efforts of teachers to manage Islamic learning at school as an effort to develop an Islamic Religious Education curriculum that aims to form a Qur'anic generation. The research method used was the descriptive qualitative method. Participants in this study were selected using a purposive sampling technique.One PAI teacher and the class he taught at SMKN 1 Rejang Lebong became the participants of the research. The data were collected using observations and interviews. The collected data wereanalysed in the following stages: data reduction, data presentation, data verification, and conclusion drawing. From the results of the study, it can be concluded that the development of Islamic religious education curriculum in shaping the Qur'anic generation is very important to implement because the current generation is the next generation of the future.